EMOTIONAL BOARD DICIPTAUNTUK MENGENALI EMOSI SISWA - Linda Wahyu S., Eko Triono, dan Muhammad Ibrahim (Pelita - Jurnal Penelitian Mahasiswa UNY, 2009)
This research aims to know 1) to what extent Emotional Board can help the teachersidentify and map the students’ emotion and 2) the use of this board to improve thestudents’ interest in learning Bahasa Indonesia at Grade VII D of MTS Negeri SumberAgung.This research was classified as research and development. The subjects of thisresearch were the teachers of Bahasa Indonesia and the students Grade VIID at MTSNSumber Agung. The techniques of the data collection were interviews, questionnaire,and observation. The data were analyzed using qualitative description.The result of the research shows that Emotional Board could be used by the teachersin mapping the emotional state, as a reference to take the appropriate steps in positiveemotional learning process, and to determine whether the learning situation is fun forthe students or not. Furthermore, Emotional Board shows significant difference whenapplied in learning activity. The students’ emotion fluctuation could lead the teachers tocreate more interesting learning.Keywords: Emotional Board, Mapping Emotion, interesting learning